KHILAFAHISME, GLOBALISASI, DAN KRISIS KEBERAGAMAN: PENDIDIKAN ISLAM MULTIKULTURAL SEBAGAI SOLUSI KONTEKSTUAL - Abdulloh; Mudhofar (Journal Multicultural of Islamic Education, 2024)
Globalization not only expands cultural and intellectual connectivity but also brings the threat of value homogenization, which erodes local identities and religious pluralism. In Indonesia, one of the serious implications is the growing influence of khilafahism a transnational ideology that rejects democracy and cultural diversity. This ideology has gained traction through digital platforms and informal education and is increasingly accepted among the younger generation. This phenomenon indicates a crisis of diversity and a disorientation of social and religious identity. This article employs a descriptive qualitative approach through library research to analyze the relationship between globalization, the spread of khilafahism, and the crisis of diversity, while also exploring the potential of multicultural Islamic education as a contextual solution. Grounded in Islamic values and the framework of maqÄá¹£id al-sharÄ«â€˜ah, multicultural Islamic education is seen as capable of instilling tolerance, inclusivity, and respect for differences. Findings indicate that the implementation of this educational model in several Islamic institutions has proven effective in shaping students' character to be moderate and open to diversity.